PENGARUH BRAND AWARENESS DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SARI ROTI DI SUKABUMI - Anjani, Dewi; Ginanjar, Noornisa sarah (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study aims to examine the effect of brand awareness and product quality on purchasing decisions for Sari Roti products in Sukabumi. The research method that the author uses is a quantitative method. The population in this study are consumers who buy and consume Sari Roti products. The sample of this research is consumers who buy and consume Sari Roti products, totaling 97 people. The type of data in this study is primary data by distributing questionnaires to respondents. Data analysis used is the validity test and instrument reliability test. The prerequisite analysis tests are the Normality Test, Multicollinearity Test, Heteroscedasticity Test and Linearity Test. Furthermore, the analysis technique uses multiple regression. The variables used are brand awareness and product quality as independent variables and purchasing decision variables as the dependent variable. Multiple linear regression model with the results of the equation Y = 6.570 +0.188 +0.130, from these results the constant is 6.750, Brand Awareness (X1) is 0.188 or 1.88% and Product Quality (X2) is 0.130 or 1.30% and Test Results t Brand awareness (X1) with results with significant t-test results <0.05, namely (0.014 <0.05) so there is a partial effect. The results of the t-test with product quality (X2) with a significant result of unit t <0.05, namely (0.01 <0.05) then there is a partial effect. Brand Awareness and Product Quality simultaneously have a positive and significant effect on Purchase Decisions for Sari Roti Products in Sukabumi as evidenced by the significant F test results in the Anova test, it is found that the Fcount value is 18.721. With a significant value of 0.000 and an F-table value of 3.09, it can be concluded that F-count > F-table with a significant level of 0.000 <0.05.